The University Library in Tromsøas a Learning Centre - Salvesen, Helge (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The University Library in Tromsø is the library of the most northerly university in the world. We have a special responsibility when it comes to taking care of and making available those documents and traditions that pertain to the northern parts of the world. It is also our goal to document and make available to a wider public the University’s own research activities. We want too to stand out as the central learning centre in the University both for students and researchers at all levels.